Analysis of a customer relationship management tool in a shipping company - Pereira, Teresa (2018)
Today’s society is technologically advanced, the world is just a click away and our companies’ customers have easy access to all the information. Therefore, they are increasingly demanding, wanting more and better at a lower cost. Using as a case study a shipping company, a system of Customer Relationship Management (CRM) was analysed to verify what reasons led to its abandonment and to realise what to do to reverse such situation. In this industry product differentiation is practically null, so the customer’s choice comes down to price. However, customers are paying more attention to customer service, therefore companies are developing stronger relationships with them. The construction of such relationships implies data collection on the client, from which one can offer services of greater value. This may lead to partnerships and competitive advantages. Thus, the use of CRM tools is being promoted for CRM tools present themselves as a valuable asset. In the end, suggestions are presented, ranging from improvements to the existing system, to more complex suggestions, costlier or breaking with the existing mode of relationship and dialogue between company and customers, but that, in the future, will certainly translate into advantages over competing companies.